Implementation of the Community Organization Supervision Policy in the Province of Dki Jakarta - Liza Aprinita; Udaya Madjid; Alma’arif (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
The important role and function of Community Organizations (Ormas) have encouraged the government to issue policies aimed at supervising Ormas activities so that they do not deviate from prevailing laws and regulations. The purpose of this study is to determine the policy implementation, supporting and inhibiting factors, as well as efforts to overcome inhibiting factors in the implementation of Community Organization Supervision Policy in the Special Capital Region of Jakarta (DKI Jakarta Province). This study employed a qualitative research method with a descriptive approach. Data collection techniques included observation, interviews, and documentation. The informants in this study consisted of 5 (five) people. Data analysis techniques included data reduction, data presentation, and conclusion drawing. The results of this study are as follows: The implementation of the Community Organization Supervision Policy in DKI Jakarta Province, viewed from the aspects of communication, resources, bureaucratic structure, and disposition, has not been effective. Supporting factors include: (a) The existence of legality, regulations, and legal frameworks in the form of technical guidelines and regulations; (b) Support from various elements of society; (c) The availability of internet-based technological sophistication as a communication medium to disseminate information, provide education, promotion, guidance, and understanding; (d) The availability of sanctions in the form of permit revocation and dissolution of organizations; (e) The existence of special institutions, namely the Provincial and Regency/City National Unity and Political Agency (Kesbangpol), which are specifically mandated and delegated to collect data, guide, and monitor the development of community organizations in the regions. The inhibiting factors include: (a) The existence of sectoral ego and apathetic attitudes within society; (b) Limited resources, both in terms of human resources and budget managed by Kesbangpol; (c) Inadequate work facilities and supporting infrastructure; (d) Low awareness, compliance, and obedience of community organizations in reporting their annual activities and organizational operations during a one-year period; (e) Weak sanctions; (f) Lack of socialization and legal counseling. Efforts to overcome the inhibiting factors include: (a) Increasing public participation and legal counseling; (b) Improving the quality and quantity of human resources; (c) Increasing budget capacity; (d) Improving the quality of work facilities and infrastructure; (e) Increasing the frequency of supervision by involving related parties and stakeholders; (f) Implementing proportional sanctions.